Ahzab suresinde din eğitimi açısından öne çıkan değerler - Güler, Medine Beyza (My University, 2019)
Değerler, her insanın içinde yer aldığı sosyal muhitin, aldığı eğitimin, istek, hedef ve gayeleri ile geçmiş bireysel tecrübelerinin mahsulüdür. Bu bireysel tasavvurun içerisinde değer algısının nasıl ve neye göre oluştuğu, değerlendirme esnasında nitelemeyi neyin sağladığı gibi hususlar din eğitiminin de gündemine aldığı konulardandır. İslâm dini, kutsal kitabı olan Kur’ân-ı Kerîm ile insanların neleri yapması ve nelerden uzak durması gerektiği konusunda onlara yol gösterme anlamında kaynağı ilahî olan ahlâkî değerler sistemi sunar. Dünyada insanın izzet ve onuruna yakışır bir düzen kurmayı hedefleyen bu değerler sisteminin asıl maksadı ise ebedî olan ahiret hayatıdır.Araştırmanın konusu olan Ahzâb sûresi de tâbi olduğu takdirde insana dünya ve ahirette mutluluk vaad eden son derece önemli prensipler içermektedir. Çalışmanın birinci bölümü kavramsal ve kuramsal çerçeveyi ihtiva etmekte, ayrıca Ahzâb sûresinde Hz. Peygamber’in (s.a.v) inananlar için model olarak sunulması sebebiyle “Değerlerin Aktarımında Model Faktörü” başlığı yer almaktadır. Bölümün son kısmında ise sûrenin genel tanıtımı yapılmıştır. İkinci bölümde sûrenin temelini oluşturan takva, itaat, ahde vefa, mahremiyet ve adalet değerleri ilk olarak Kur’an’da, sonra ise Ahzâb sûresinde vurgu yapılan âyetlerde geçtiği şekliyle ele alınmış, din eğitimi açısından değerlendirilmiştir.

Values are the outcome of the social environment which each person is involved in, the education they’ve received, their wishes, goals, and aims accompanied by their past personal experiences. According to this individual conception; how the perception of value is formed, what it is based on, and what makes it possible to qualify during the evaluation are issues that are also contextualized by religions education. The religion of Islam offers a system of moral values with a divine source in terms of guiding people about what they must do and what they must avoid in the light of Quran. The main purpose of the system of values, which aims to establish an order that is worthy of dignity and honor of human being in the world, is the life in the hereafter.Surah al-Ahzab as the subject of the study contains highly important principles that promise happiness both in the world and in the hereafter if people subject to it. The first chapter of the study contains the conceptual and theoretical framework. In addition to this, since Prophet Muhammad (s.a.w) is presented as a role model and his relations with his family occupy an important place in the Surah al-Ahzab, the title of The Role Model Factor in the Transmission of Values is included in the first chapter. At the end of the chapter, the general introduction of the Surah al-Ahzab was made. In the second chapter, the values that underlie the surah such as taqwa, obedience, faithfulness, privacy and justice are taken firstly in the Qur’an and then in the verses emphasized in the Surah al-Ahzab, and were evaluated in terms of religious education.
Keywords: Ahzâb Sûresi; Değerler; Din eğitimi; Din Eğitimi Surah al-Ahzab; Felsefe ve din; Islam; İslam; Philosophy and religion; Religious education; Values